Plasma Norepinephrine in Hypertensive Rats Reflects α2-Adrenoceptor Release Control Only When Re-Uptake is Inhibited - Berg, Torill; Walaas, Sven Ivar; Roberg, Bjørg Åse; Huynh, Trang Thi; Jensen, Jørgen (Frontiers in Neurology, 2012)
α2 adrenoceptors (AR) lower central sympathetic output and peripheral catecholamine release, thereby protecting against sympathetic hyperactivity and hypertension. Norepinephrine re-uptake transporter effectively (NET) removes norepinephrine from the synapse. Overflow to plasma will therefore not reflect release. Here we tested if inhibition of re-uptake allowed presynaptic α2AR release-control to be reflected as differences in norepinephrine overflow in anesthetized hypertensive (SHR) and normotensive (WKY) rats. We also tested if α2AR modulated the experiment-induced epinephrine secretion, and a phenylephrine-induced, α1-adrenergic vasoconstriction. Blood pressure was recorded through a femoral artery catheter, and cardiac output by ascending aorta flow. After pre-treatment with NET inhibitor (desipramine), and/or α2AR antagonist (yohimbine, L-659,066) or agonist (clonidine, ST-91), we injected phenylephrine. Arterial blood was sampled 15 min later. Plasma catecholamine concentrations were not influenced by phenylephrine, and therefore reflected effects of pre-treatment. Desipramine and α2AR antagonist separately had little effect on norepinephrine overflow. Combined, they increased norepinephrine overflow, particularly in SHR. Clonidine, but not ST-91, reduced, and pertussis toxin increased norepinephrine overflow in SHR and epinephrine secretion in both strains. L-659,066+clonidine (central α2AR-stimulation) normalized the high blood pressure, heart rate and vascular tension in SHR. α2AR antagonists reduced phenylephrine induced vasoconstriction equally in WKY and SHR. Conclusions: α2AAR inhibition increased norepinephrine overflow only when re-uptake was blocked, and then with particular efficacy in SHR, possibly due to their high sympathetic tone. α2AAR inhibited epinephrine secretion, particularly in SHR. α2AAR supported α1AR-induced vasoconstriction equally in the two strains. α2AR malfunctions were therefore not detected in SHR under this basal condition.